PERANCANGAN SISTEM INFORMASI PENGELOLAAN PERSEDIAAN ALAT DAN BAHAN PERTANIAN STUDI KASUS PADA UD. PELAWI BERASTAGI - Surbakti, Wahyu Irmanto; Hutapea, Marlyna Infryanty; Purba, Eviyanti Novita (Universitas Methodist Indonesia, 2023)
The data-management information system of supply goods played a significant role in running a business. This system is used to input inventory data into the database so there are no internal errors in input, output and report creation based on data that desirable. But in the UD. Pelawi had not been able to supply computerized supply management systems and therefore had not been able to control the available supply of goods. What goes in and out is recorded by the employee using the supply book. This was done by the attendant by hand with the inventory book, so the record was often misplaced. That would create some of the problems, such as wasted time and heavy paper sheets, would result in hard-finding data. There has been no encoding of the item which suggests the item entered first. Therefore in compiling this final assignment the writer took the FIFO method on the UD. Pelawi's supply research. Which through this method will create a useful code for figuring out which goes first in the cellar, which will be sold in order to maintain the quality of the item. It is also hoped that it will enable better company activities and data storage so that better research and report making processes are more effective and efficient.